The effect of logistic services on the watermelon value chain in Tanzania. Issue 7 (3rd October 2017) - Makuya, Victoria; Mpenda, Zenna; Ndyetabula, Daniel
ABSTRACT: This article reports on a study that aimed to understand the effects for poverty reduction of the link between logistic services and cost of the watermelon value chain in Rufiji and Mkuranga districts in Tanzania. Structured questionnaires and FGDs were used to collect data from 251 respondents. Findings revealed that transport cost, storage cost, purchase cost, and logistics service have strong significant effect on the watermelon value chain cost. Based on the findings, the study recommended the use of affordable methods of storage, opening agro-input shops in villages, and the development of a favourable environment for watermelon businesses, to help reduce chain cost.